1979
DOI: 10.1017/s0074180900014388
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime of density waves and classification of spirals

Abstract: Checking the density-wave theory against observations of our own Galaxy has proven very difficult, as witnessed also at this Symposium. Less ambiguous results, however, are obtained for other galaxies. These results involve a) calculating convincing models for a sample of 25 fairly well observed spirals (Roberts et al. 1975) and b) locating the compression zones on the inner edges of the spiral arms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

1980
1980
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 1 publication
1
16
0
4
Order By: Relevance
“…3,1. DATENMATERIAL Das Datenmaterial (1323 Radialgeschwindigkeiten) ist in einem Katalog zusammengefaBt (Feitzinger und Weiss, 1979).…”
Section: Kinematik Und Dynamik Der Groflen Magellanschen Wolkeunclassified
See 3 more Smart Citations
“…3,1. DATENMATERIAL Das Datenmaterial (1323 Radialgeschwindigkeiten) ist in einem Katalog zusammengefaBt (Feitzinger und Weiss, 1979).…”
Section: Kinematik Und Dynamik Der Groflen Magellanschen Wolkeunclassified
“…Die Mitte der Kreisringbereiche (AR = 0~ gemessen in Grad, ist jeweils rechts oben markiert. GMW (R = 2?5) ist 0o = 188 ~ in bester Obereinstimmung mit den yon Feitzinger et al (1977) mit einer kleineren Datenmenge und der Gradientenmethode abgeleiteten Wert. Diese Obereinstimmung zeigt die Konsistenz der Methoden und die Verl/iBlichkeit der N/iherungsverfahren und Wichtungen.…”
Section: V(r O) = Vs + E(r O)unclassified
See 2 more Smart Citations
“…The inner arcsecond of R136, denoted R136a, is unresolvable by conventional ground‐based telescopes, and it was suspected that R136a is in fact a single stellar object of more than 3000 M ⊙ (Feitzinger et al 1980; Cassinelli, Mathis & Savage 1981). However, careful ground‐based work (both direct imaging: Moffat & Seggewiss 1983; Moffat, Seggewiss & Shara 1985 and speckle interferometry: Weigelt & Baier 1985) showed that R136a was not a single star.…”
Section: Introductionmentioning
confidence: 99%